2003
DOI: 10.1103/physrevlett.90.036803
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Landau Levels and Interactions in Low-Lying Excitations of Composite Fermions at1/3ν2/5

Abstract: Excitation modes in the range 2/5>or=nu>or=1/3 of the fractional quantum Hall regime are observed by resonant inelastic light scattering. Spectra of spin-reversed excitations suggest a structure of lowest spin-split Landau levels of composite fermions that is similar to that of electrons. Spin-flip energies determined from spectra reveal significant composite fermion interactions. The filling factor dependence of mode energies displays an abrupt change in the middle of the range when there is partial populatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
57
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 38 publications
(63 citation statements)
references
References 29 publications
(67 reference statements)
6
57
0
Order By: Relevance
“…The bare Zeeman energy was obtained from spectra such as those in Figs. 3 and 4(a), where E Z is given by the position of the peaks labeled SW. With these determinations it was found that E ↑↓ ∼ = 0.054E c [24]. The measurement of the total spin reversal energy E * Z from the spin wave mode at q → ∞, as shown in Fig.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The bare Zeeman energy was obtained from spectra such as those in Figs. 3 and 4(a), where E Z is given by the position of the peaks labeled SW. With these determinations it was found that E ↑↓ ∼ = 0.054E c [24]. The measurement of the total spin reversal energy E * Z from the spin wave mode at q → ∞, as shown in Fig.…”
mentioning
confidence: 99%
“…Although there is considerable difference in density, both samples show a similar behavior. The figure reveals that an excitation derived from the SF roton at ν = 2/5 [11,24], the mode labelled SF − , shifts to lower energies as the second level starts to depopulate for ν 2/5, and disappears for filling factors in the middle of the range 2/5 ≥ ν ≥ 1/3. At larger magnetic fields, ν 1/3, a narrow peak (SF + ) appears below the SW.…”
mentioning
confidence: 99%
See 3 more Smart Citations